Evaluating SHIFT: a game-based learning application for teaching the afterlife in Islamic education - Abu Hassan, Muhammad Ikram; Tunku Ahmad, Tunku Badariah (IIUM Press, 2026)
This is a pilot study that examines the effect of SHIFT (Stairway to Heaven in Islamic Faith), a game-based learning application, on university students’ conceptual understanding of the afterlife, a core component of Islamic faith taught in Islamic Education (ISED). Belief in the hereafter is a fundamental concept in Islam but it is often conveyed through conventional instructional approaches that provide limited opportunities for active engagement and deep understanding. SHIFT was developed to address this gap by presenting the stages of life after death—from worldly life (dunia) to judgment and the hereafter—through interactive multimedia and formative questions aimed to instill students’ understanding of the afterlife. The study employed a pre-experimental one-group pretest–posttest design involving 25 male undergraduate students from Year 1 to Year 4 at the International Islamic University Malaysia (IIUM). Students’ conceptual understanding of the afterlife was measured using a 10-item self-developed open-ended test, with scoring reliability established through inter-rater correlation. Data were analyzed using a paired-samples t-test. Results revealed a statistically significant improvement in students’ conceptual understanding following the intervention, with a large effect size (Cohen’s d = 0.73). These findings provide preliminary evidence that game-based learning applications such as SHIFT can effectively support the teaching of abstract and profound concepts in Islamic Education at the university level